Assessment of postural risks in adolescents aged 12-19 during smartphone use - Kurnia, Fikrihadi; Triadi, Anak Agung Alit; Suartika, I Made; Wijana, Made; Pradityatama, Maharsa (Journal Industrial Servicess, 2024)
In contemporary times, the use of smartphones has become an essential requirement for daily life in the digital era. The prevalent consequences of smartphone usage include the development of poor posture and behaviors. This study aimed to assess the risk of musculoskeletal disorders (MSD) among smartphone users, focusing on adolescents aged 12 to 19 years. A sample of 82 students (79.3% female and 20.7% male, with an average age of 15.7 ± 2 years and a normal BMI of 76.8%) in the West Lombok district of the West Nusa Tenggara Province in Indonesia was measured. Data collection through simple random sampling involved distributing questionnaires to participants and requesting them to provide responses based on their personal experiences. The present study employs a chi-square analysis to examine the association between smartphone usage, posture behavior, and the highest values of MSD complaints. The findings indicate that the neck (46.3%) and back (45.1%) were the body regions with the most prevalent complaints of MSD. The participants frequently engaged in standing without support and walking as their posture behaviors. There was a significant correlation between the level of neck pain and posture during walking. The use of smartphones among adolescents has an impact on the risk level of experiencing MSD complaints, thereby increasing the potential for illness and abnormalities. Hence, it is necessary to exercise sufficient control over the routine usage of smartphones to mitigate the negative impacts incurred.